OPTIMIZATION AND COMPARISON STUDY OF THE USE OF TIO2 AND SNO2 AS ELECTRON TRANSPORT LAYER IN HOLE TRANSPORT LAYER-FREE METHYLAMMONIUM LEAD IODIDE PEROVSKITE SOLAR CELL - Zaidan, Athallah
The depletion of fossil fuels and the need for energy is rising leaving the world struggling to meet the energy shortage. Among all the renewable energy resources available on the earth, solar energy is one of the best solutions to respond to the depletion of fossil fuel reserves. Perovskite solar cells have been attractive due to their low cost and high efficiency. Wide-bandgap inorganic semiconductor materials have been material of choice for the electron transport layer (ETL) with TiO2 as the most widely used material to date. However, TiO2 needs to be processed at high temperature to obtain its excellent electronic properties. Alternative ETL material such as SnO2 has been proposed, which could be fabricated at low cost and produce lower hysteresis index. In this study, we compare the performance of TiO2 ETLs from different fabrication methods with SnO2 and study the effects of the variation. The fabrication of ETL started with the variation of the amount of spin-coating. The spin-coating methods were varied by 1-, 3-, and 5-time spin-coating to investigate the optimum conditions. Then, the optimum amount of spin-coating method was compared with the chemical bath deposition method in order to obtain perovskite solar cell with TiO2 ETL that produced the best photovoltaic performances. Finally, the best TiO2 fabrication method was compared with SnO2 with various configurations. The experimental results showed that the perovskite solar cell with optimum performance was achieved with TiO2 compact layer that deposited using 3-time spin-coating with PCE, open circuit voltage, and short circuit current density of 8.94%, 974.1 mV, and 16.73 mA/cm2, respectively. There was a tendency of increase the photovoltaic performances from 1-time to 3-times spin-coating, thus increasing the amount of spin-coating from 3-time to 5-time ended up lowering the photovoltaic performance. The cells produced using spin-coating method provided better photovoltaic performance than that of chemical bath deposition method with PCE, open circuit voltage, and short circuit voltage of 3.37%, 598.8 mV, and 13.96 mA/cm2, respectively. Overall, the samples prepared with chemical bath deposition method had lower hysteresis index of 35.09% than those of spin-coating method with hysteresis index of 37.69%. The second part of this work shows that the perovskite solar cell with planar SnO2 exhibited better photovoltaic performance than those with planar TiO2. Furthermore, samples with double layer TiO2/SnO2 provided better photovoltaic performance than those with both planar SnO2 and TiO2. Yet, the best photovoltaic performance was obtained by the sample with mesoscopic structures of TiO2 that was fabricated using spin-coating method.